Measurement properties of self-report questionnaires on health-related quality of life and functional health status in dysphonia: a systematic review using the COSMIN taxonomy. - Speyer, R.; Kim, J.; Doma, K.; Chen, Y.; Denman, D.; Phyland, D.; Parsons, L.; Cordier, Reinie (2018)
PURPOSE: The current review was conducted to identify all self-report questionnaires on functional health status (FHS) and/or health-related quality-of-life (HR-QoL) in adult populations with dysphonia (voice problems), and to evaluate the psychometric properties of the retrieved questionnaires. METHODS: A systematic review was performed in the electronic literature databases PubMed and Embase. The psychometric properties of the questionnaires were determined using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) taxonomy and checklist. Responsiveness was outside the scope of this review and as no agreed 'gold standard' measures are available in the field of FHS and HR-QoL in dysphonia, criterion validity was not assessed. Only questionnaires developed and published in English were included. RESULTS: Forty-eight studies reported on the psychometric properties of 15 identified questionnaires. As many psychometric data were missing or resulted from biased study designs or statistical analyses, only preliminary conclusions can be drawn. Based on the current available psychometric evidence in the literature, the Voice Handicap Index seems to be the most promising questionnaire, followed by the Vocal Performance Questionnaire. CONCLUSIONS: More research is needed to complete missing data on psychometric properties of existing questionnaires in FHS and/or HR-QoL. Further, when developing new questionnaires, the use of item response theory is preferred above classical testing theory, as well as international consensus-based psychometric definitions and criteria to avoid bias in outcome data on measurement properties.